The Collected Short Stories of Bharati Mukherjee, edited by Ruth Maxey. Temple University Press: Philadelphia, 2023, pp. 408. - Crespo Gómez, Ana María (Complutense Journal of English Studies, 2024)
The Collected Short Stories of Bharati Mukherjee, edited by Ruth Maxey. Temple University Press: Philadelphia, 2023, pp. 408.